The Conditions of Granting a License to Practice the Activity of the Investment Capital Company in the Algerian Legislation - Ahmouda, Khaoula; Mahmoudi, Bachir (Journal of Legal Studies and Researches, 2024)
This paper focuses on the conditions laid down by the Algerian legislator for obtaining a license for venture capital companies to exercise their financial activity. The latter is one of the most important modern financing techniques for SMEs. Therefore, through Law 06/11, the legislator subjected them to several rules so that they can proceed with their activity after obtaining the license by the responsible authority.